CD300b regulates intestinal inflammation and promotes repair in colitis - Avlas, Shmuel; Kassis, Hala; Itan, Michal; Reichman, Hadar; Dolitzky, Avishay; Hazut, Inbal; Grisaru-Tal, Sharon; Gordon, Yaara; Tsarfaty, Ilan; Karo-Atar, Danielle; Rozenberg, Perri; Bitton, Almog; et al. (Frontiers in Immunology, 2023)
Chronic inflammation is a hallmark charataristic of various inflammatory diseases including inflammatory bowel disease. Subsequently, current therapeutic approaches target immune-mediated pathways as means for therapeutic intervention and promotion of mucosal healing and repair. Emerging data demonstrate important roles for CD300 receptor family members in settings of innate immunity as well as in allergic and autoimmune diseases. One of the main pathways mediating the activities of CD300 family members is via promotion of resolution through interactions with ligands expressed by viruses, bacteria, or dead cells (e.g., phospholipids such as PtdSer and/or ceramide). We have recently shown that the expression of CD300a, CD300b and CD300f were elevated in patients with IBD and that CD300f (but not CD300a) regulates colonic inflammation in response to dextran sodium sulphate (DSS)-induced colitis. Whether CD300b has a role in colitis or mucosal healing is largely unknown. Herein, we demonstrate a central and distinct role for CD300b in colonic inflammation and subsequent repair. We show that Cd300b-/- mice display defects in mucosal healing upon cessation of DSS treatment. Cd300b-/- mice display increased weight loss and disease activity index, which is accompanied by increased colonic histopathology, increased infiltration of inflammatory cells and expression of multiple pro-inflammatory upon cessation of DSS cytokines. Furthermore, we demonstrate that soluble CD300b (sCD300b) is increased in the colons of DSS-treated mice and establish that CD300b can bind mouse and human epithelial cells. Finally, we show that CD300b decreases epithelial EpCAM expression, promotes epithelial cell motility and wound healing. These data highlight a key role for CD300b in colonic inflammation and repair processes and suggest that CD300b may be a future therapeutic target in inflammatory GI diseases.